Sexual violence in trials for crimes against humanity in Argentina and Uruguay - Victoria Alvarez (Sortuz)
As in other dictatorships in the Southern Cone, during the last military dictatorships in Argentina (1976-1983) and Uruguay (1973-1985), women prisoners were victims of different forms of sexual violence. In Argentina, only in recent years, after the reopening of trials for crimes against humanity and with considerable resistance, the possibility of trying sexual violence as a crime distinct from torture began to be considered, and in 2010 the first conviction for this crime was handed down. In 2011, a criminal complaint was filed for the first time for rape and sexual abuse committed during the period of the Uruguayan military dictatorship made collectively by 28 former female political prisoners. In this paper we will describe the paths taken by the justice system in each of the countries and the changing moments of memory in order to finally analyze the process of shaping and organizing these complaints and to report on the main legal debates about the possibility of prosecuting these crimes in both countries. Studying the Argentine and Uruguayan cases together will allow us to address the specific characteristics of each national historical development but, at the same time, will seek to account for a process that exceeds national boundaries.